PENAMBAHAN PERTURBATION TRAINING PADA CORE STABILITY EXERCISE LEBIH BAIK DARIPADA CORE STABILITY EXERCISE DALAM PENINGKATAN KESEIMBANGAN LANSIA DI MENGWI-BADUNG - Putu Mulya Kharismawan; RA Tuty Kuswardhani; Wahyuddin -; Anak Agung Sagung Sawitri; I Nyoman Adiputra; S. Indra Lesmana (Sport and Fitness Journal, 2019)
Background: falls is one of the major problems that often occur in the elderly population. It caused the decrease of balance in elderly. Purpose: to prove addition perturbation training on core stability exercise better than core stability exercise to improve balance in elderly. Method: This research is an experiment research design with pre and post test control group design. These samples included 22 people who were divided into two groups. Group 1 has given perturbation training and core stability exercise, while Group 2 has given core stability exercise. Measurement of balance measured using a Berg balance scale. Result: Paired t-test at Group 1 and Group 2 showed value p=0.001 (p<0.025), this results showed a significant balance increase in each groups. Then independent sample t-test between Group 1 and Group 2 showed value of p=0.015 (p<0.025). It results showed significant difference between Group 1 and Group 2. Conclusion: additional perturbation training on core stability exercise better than core stability exercise to improve balance in elderly.